Integration Of Mother Language And Reading Subjects In Solving Mathematical Problems In Primary Education - Iskandarova J. J. (Genius Journals, 2025)
This article discusses the importance of the mother tongue and reading subjects in teaching mathematical literacy in primary grades. Basically, it provides an understanding of mathematics teaching methodology and its advantages.
Keywords: mathematics; integration; methodology